Potentiometric Studies of Binary and Ternary Nickel(II) Complexes Involving Ethylenediamine-N,N´ -Diacetic Acid, Amino Acids and Peptides - M. SHOUKRY, EMAN; H. ABD EL-WAHAB, ZINAB; A. ALI, REDA (Asian Journal of Chemistry, 2010)
The formation equilibria of binary and ternary complexes of nickel(II) with ethylenediamine-N,N'-diacetic acid (EDDA) as primary ligand and amino acid or peptide (HL) as secondary ligand have been investigated. Stoichiometries and stability constants of the complexes were determined at 25°C and 0.1 M NaNO3 ionic strength. The hydrolysis of the Ni (EDDA) complex and the deprotonation of the amide residue in the peptide complexes are discussed in relation to physiological conditions.